Opioid pathways in an avian retina. II. Synaptic organization of enkephalin-immunoreactive amacrine cells - Watt, CB (J Neurosci, 1985)
Peroxidase-antiperoxidase immunocytochemistry was utilized to investigate the synaptic organization of enkephalin-like immunoreactive amacrine (Enk-amacrine) cells in the chicken retina. An initial light microscopic analysis revealed that immunostained cell bodies were situated in either the second or third tier of cells from the border of the inner nuclear and inner plexiform layers. The processes of such cells extended into the inner plexiform layer where they ramified as a fine plexus in sublaminae 1 and 3 to 5. At the ultrastructural level, enkephalin-positive somas exhibited a rather dense and evenly distributed peroxidase reaction product throughout their cytoplasm. Furthermore, the nucleus of Enk-amacrine cells was characterized by a round, unindented nuclear membrane. Immunoreactive processes of such cells were found to receive synaptic input from unstained amacrine and bipolar cells. Immunolabeled varicosities formed conventional synaptic contacts onto other vesicle-filled, nonimmunoreactive profiles tentatively suggested to originate from amacrine cells. Bipolar cell terminals did not receive synaptic input from stained varicosities of enkephalin-immunoreactive amacrine cells. Moreover, each of the above synaptic relationships were identified in each of sublaminae 1, and 3 to 5 of the inner plexiform layer. In addition, labeled varicosities of Enk-amacrine cells synapsed upon unstained processes which lacked synaptic vesicles and possibly arise from ganglion cells. Enkephalin- positive processes were also observed to synapse upon the vitreal pole of unstained somas situated in the innermost cell row of the inner nuclear layer. Lastly, large immunoreactive varicosities of Enk- amacrine cells were often characterized by the presence of large dense- core vesicles in addition to typical, small agranular synaptic vesicles.